The future of human rights - Baxi, Upendra (New Delhi ; Oxford : Oxford University Press, 2008)
This book critically examines the contemporary discourses on the nature of 'human rights', their histories, the myths that are embedded in them, and contributes an alternative reading of those histories by placing the concerns and interests of the 'people in struggle and communities of resistance' at centre stage.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Human rights; Human rights -- History